Distribution of equivalent potential temperature in the Field of monsoon depressions - CHOWDHURY, A. (MAUSAM, 1983)
Spatial variation in the structure of the depression as portrayed by equivalent potential temperature has been examined in this paper. Areas of enhanced and suppressed convection have been identified. Height to which the cumulonimbus tops could penetrate have been obtained and compared with those actually observed. Upper air temperatures have also been computed and compared with the mean monsoon atmosphere. Zones of high and low relative humidity have been demarcated and its relationship with convective areas, established and discussed.